Low pressure UV/H2O2 treatment for the degradation of the pesticides metaldehyde, clopyralid and mecoprop – Kinetics and reaction product formation. (15th March 2016) - Semitsoglou-Tsiapou, Sofia; Templeton, Michael R.; Graham, Nigel J.D.; Hernández Leal, Lucía; Martijn, Bram J.; Royce, Alan; Kruithof, Joop C.
Abstract: The degradation kinetics of three pesticides – metaldehyde, clopyralid and mecoprop – by ultraviolet photolysis and hydroxyl radical oxidation by low pressure ultraviolet hydrogen peroxide (LP-UV/H2 O2 ) advanced oxidation was determined. Mecoprop was susceptible to both LP-UV photolysis and hydroxyl radical oxidation, and exhibited the fastest degradation kinetics, achieving 99.6% (2.4-log) degradation with a UV fluence of 800 mJ/cm 2 and 5 mg/L hydrogen peroxide. Metaldehyde was poorly degraded by LP-UV photolysis while 97.7% (1.6-log) degradation was achieved with LP-UV/H2 O2 treatment at the maximum tested UV fluence of 1000 mJ/cm 2 and 15 mg/L hydrogen peroxide. Clopyralid was hardly susceptible to LP-UV photolysis and exhibited the lowest degradation by LP-UV/H2 O2 among the three pesticides. The second-order reaction rate constants for the reactions between the pesticides and OH-radicals were calculated applying a kinetic model for LP-UV/H2 O2 treatment to be 3.6 × 10 8, 2.0 × 10 8 and 1.1 × 10 9 M −1 s −1 for metaldehyde, clopyralid and mecoprop, respectively. The main LP-UV photolysis reaction product from mecoprop was 2-(4-hydroxy-2-methylphenoxy) propanoic acid, while photo-oxidation by LP-UV/H2 O2 treatment formed several oxidation products. The photo-oxidation of clopyralid involved either hydroxylation or dechlorination of the ring, while metaldehyde underwent hydroxylation and produced acetic acid as a major end product. Based on the findings, degradation pathways for the three pesticides by LP-UV/H2 O2 treatment were proposed. Graphical abstract: Highlights: The degradation order observed for LP-UV/H2 O2 was mecoprop > metaldehyde > clopyralid. The same degradation order was observed for the reaction with the OH-radicals. Clopyralid exhibited the largest enhancement in kinetics with H2 O2 addition. Mecoprop produced one photolysis product and smaller ones from OH-radical attack. Clopyralid and metaldehyde produced mainly hydroxylated products.